2011
DOI: 10.1016/j.ejcts.2010.12.030
|View full text |Cite
|
Sign up to set email alerts
|

High-dose tranexamic acid is related to increased risk of generalized seizures after aortic valve replacement

Abstract: Our results indicate that high-dose TXA is associated with an increased incidence of postoperative generalized seizures in patients undergoing AVR compared with EACA, especially when suffering from renal impairment. A possible association between recombinant activated factor VIIa and the occurrence of postoperative seizures needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 24 publications
(34 reference statements)
0
81
1
1
Order By: Relevance
“…Tranexamic acid has traditionally been considered a safe drug with a reported low incidence of adverse events. More recently, several investigators have suggested highdose tranexamic acid to be aetiological in postoperative seizures following cardiac surgery especially in patients with renal dysfunction [7][8][9][10][11]. Murkin et al observed an increase in the incidence of postoperative seizures following administration of high-dose tranexamic acid (up to 259 mg.kg ) at centres in Canada and the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tranexamic acid has traditionally been considered a safe drug with a reported low incidence of adverse events. More recently, several investigators have suggested highdose tranexamic acid to be aetiological in postoperative seizures following cardiac surgery especially in patients with renal dysfunction [7][8][9][10][11]. Murkin et al observed an increase in the incidence of postoperative seizures following administration of high-dose tranexamic acid (up to 259 mg.kg ) at centres in Canada and the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…seizures in cardiac surgical patients [7][8][9][10][11]. Following the publication of a randomised controlled trial examining the use of antifibrinolytic agents in high-risk cardiac surgical patients (Blood Conservation Using Antifibrinolytics in a Randomised Trial (BART)), and the subsequent restriction of the use of aprotinin, tranexamic acid is currently a widely used antifibrinolytic agent in cardiac surgery [5].…”
Section: Discussionmentioning
confidence: 99%
“…TXA-associated seizures occur most frequently as patients emerge from general anesthesia in the early postoperative period (23,24,27,59). Thus, we postulated that the prototypic general anesthetics isoflurane (60) and propofol (39) would attenuate TXA inhibition of glycine receptors.…”
Section: Figurementioning
confidence: 99%
“…More recently, TXA has been associated with an increased incidence of postoperative seizures in cardiac patients (23,24). Historically, postoperative seizures have occurred in about 0.5%-1% of cardiac patients (25,26), but the use of higher doses of TXA has been associated with a higher incidence of seizures (2.7%-7.6%) (27,28), primarily of the grand mal type (23,29).…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of seizures after adult cardiac surgery is 0.5-7.6% [1][2][3][4][5][6][7][8]. The aetiology of postoperative seizures is often multifactorial, and causes range from benign metabolic disturbance to cerebrovascular accident.…”
Section: Introductionmentioning
confidence: 99%